Photocatalytic of Thiophene Desulfurization - Mohd Makhtar, Siti Nurfatin Nadhirah; Hairom, Nur Hanis Hayati; Puasa, Nor Aliffah; Madon, Rais Hanizam (Emerging Advances in Integrated Technology, 2023)
Thiophene, found in the fuels is a heterocyclic five-membered ring consisting of sulfur as the heteroatom, with two pairs of electrons at the S atom along with a pair in the six-electron ?-system and the others in the ring. Thiophene give negative impacts on living things and also the atmosphere. The presence of sulfur in fuels will lead to the emission of sulfur dioxide into the atmosphere and lead to atmospheric pollution such as acid rain. Thiophene is difficult to remove by using conventional desulfurization processes such as hydro-sulfurization (HDS). Thus, the photocatalytic process is the best alternative method available to degrade thiophene. The photocatalytic process only requires a minimal quantity of catalyst and the by product is almost zero or less harmful to the environment and living things. The process efficiency depends strongly on the chosen photocatalyst. ZnO/KCC provides great potential as the photocatalyst. Hence, this review paper focus on photocatalytic thiophene desulfurization using ZnO/KCC as the photocatalyst.